The relationship between genital hygiene behaviors and genital infections among women: A systematic review - Afriza Umami; Edit Paulik; Regina Molnár; Bhisma Murti (Jurnal Ners, 2022)
Introduction: Genital hygiene is an important part of women’s health and is essential for protecting reproductive health. Women adopt many genital hygiene behaviors, which will have direct and indirect effects on genitals and possible sexually transmitted infections. This systematic literature review aimed to know the types of genital hygiene behaviors practiced by women and assess the relationship between genital hygiene behavior and genital infection. Methods: A systematic search of the electronic databases, PubMed, Ovid, Web of Science, Scopus, ScienceDirect, JSTOR, and SAGE, for literature published between January 2001 and 2021. The keywords used were “genital hygiene behavior” AND “genital infections” AND “women OR female.” The inclusion criteria focused on genital hygiene behavior and the incidence of genital infection. The included full papers with observational research methods followed the PRISMA guidelines. After reading the full content of the included studies, key themes and concepts were extracted and synthesized. Results: In total 383 articles were screened. Five articles met the inclusion criteria and were analyzed. The analysis revealed four categories related to genital hygiene behavior among women: underwear hygiene, bathing habits, menstrual hygiene, and coital hygiene. Genital infections included bacterial vaginosis, trichomoniasis, and vulvovaginal candidiasis. The review showed that incorrect and inadequate genital hygiene behavior increases the risk of vaginal infection. Conclusion: A higher incidence of genital infections occurred in women with improper genital hygiene practices. It is necessary for health professionals to educate women about good genital hygiene practices in order to reduce the rate of genital infections.